2011
DOI: 10.1002/fam.1107
|View full text |Cite
|
Sign up to set email alerts
|

High strength retention and dimensional stability of silicone/alumina composite panel under fire

Abstract: SUMMARY Compact silicone/alumina composite was obtained by highly filling aluminum oxides and hydroxides in silicone resin. The flexural strength and dimensional change of the silicone/alumina composite after being fired has have been studied. It presented a special fire resistance, which could well coordinate the contradiction between the mechanical strength retention and the dimensional stability of silicone‐based composite in case of catching fire. Thermogravimetric analysis, scanning electron microscopy, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Ceramization effect is based on sticking mineral particles dispersed in polymer matrix together in different processes, generally in the presence of fluxing agent [1][2][3][4][5][6][7][8]. Even without the addition of inorganic filler of relatively low softening point temperature (fluxing agent like glass oxide frits), the effect of fire char formation can be observed, but its durability and shape preservation leave much to be desired, especially when ceramization occurs at quite low temperature (550-800°C) [9][10][11][12][13][14][15]. Polymer materials (especially based on fully organic thermoplastics or elastomers) exposed to fire undergo strong thermal degradation and destruction [16][17][18][19][20][21] very often accompanied by the effect of burning drops, which can significantly increase the spread of flames [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceramization effect is based on sticking mineral particles dispersed in polymer matrix together in different processes, generally in the presence of fluxing agent [1][2][3][4][5][6][7][8]. Even without the addition of inorganic filler of relatively low softening point temperature (fluxing agent like glass oxide frits), the effect of fire char formation can be observed, but its durability and shape preservation leave much to be desired, especially when ceramization occurs at quite low temperature (550-800°C) [9][10][11][12][13][14][15]. Polymer materials (especially based on fully organic thermoplastics or elastomers) exposed to fire undergo strong thermal degradation and destruction [16][17][18][19][20][21] very often accompanied by the effect of burning drops, which can significantly increase the spread of flames [22].…”
Section: Introductionmentioning
confidence: 99%
“…The composites exposed to flames and elevated temperature create ceramic phase protecting wire and ensure electric integration of the circuit up to 120 min. The family of these materials is still increasing, being the result of more and more research devoted to this issue [1][2][3][4][5][6][7][8][9][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Wang J. et al developed a glassy frit facilitating ceramification of remarkably low softening point temperature of 400°C [15]. Whereas Xiong et al proposed a solid-state sintering mechanism as an explanation of highly loaded silicone composites ceramification [16]. Many studies describe effects of incorporation of different additives on properties of ceramifiable silicone composites, such as organic and mineral fibers [17], carbon fibers [18], organo-modified montmorillonites (O-MMT) [19], cenospheres covered with iron [20,21] or silsesquioxanes [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Sintering of mineral filler particles due to condensation of hydroxyl groups present on their surface [16,40]. (3) Synthesis of new mineral phases as a result of reaction between refractory filler particles and silica produced caused by thermooxidative degradation of silicone matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Creation of the ceramic structure can take place in several ways: (1) formation of a continuous and porous structure involving amorphous fluxing agent, which softens in elevated temperature and sticks thermally stable mineral particles together [10], (2) creation of silica connections between particles of mineral filler during thermooxidative degradation of silicone matrix [11,12] and (3) creation of silicon oxycarbide (SiOC) ceramic phase due to deposition, crosslinking and volatilization of siloxane macromolecules on the surface of reinforcing silica particles dispersed in silicone matrix in the presence of platinum complex [13]. showed that also boro-siloxanes can be used as efficient fluxing agent even for organic polymers [15].…”
Section: Introductionmentioning
confidence: 99%